A study on predictive risk of asymptomatic gallstones among diabetic group of patients in HUSM - Alwi, Ahmad Fais Mukriz (2017)
Background: Gallstones disease and diabetes mellitus is a common disease in the modern society. There is no epidemiological data published about gallstone disease in Malaysia. Western data showed that about 20 to 25 million people or 10 to 15% of adult population had gallstone disease (Stinton et al., 2010). Many of them about 50 to 70% are asymptomatic at the time of diagnosis (Sakorafas et al., 2007). In Malaysia, the recognition of importance to manage this disease had led Ministry of Health Malaysia to produce the clinical practice guidelines in 1997. Diabetes mellitus is well-known risk factors for developing gallstones (Méndez-Sánchez et al., 2005c). In Malaysia, prevalence of diabetes mellitus had increased from 15% in 2011 to 17.5% in 2015 based on recent National Health and Morbidity Survey (Health, 2015). The morbidity from the complications of acute biliary disease and post operative is higher in diabetic patient compared to non diabetics (Agarwal et al., 2015). Aims and objectives: Aim for this retrospective study is to identify relationship between risk factors to the development of gallstones disease. The objectives of this study are to find prevalence of the asymptomatic gallstones disease and to find the association of risk factors; age, gender, BMI, parity, family history, HbA1c and duration of diabetes mellitus between the diabetic and non-diabetic patient. Identification of risk factors will help to conduct a screening in diabetic patient. Thus, appropriate treatment will be commenced early and the complications of gallstones disease will be reduced.Patients and methods: This cross sectional study was conducted at Hospital Universiti Sains Malaysia from August 2013 until December 2014. 143 patients who are asymptomatic from gallstone disease were recruited. They were identified from ultrasound abdomen examination, which they underwent for other causes and accidentally found to have gallstones. 73 patients were in diabetic group while 70 patients in control group. In diabetic group, 37 patients were male and 36 patients were female. In control group, 47 patients were female and 23 patients were male. The retrospective data was collected by a single researcher and analysed in SPSS Version 22. Statistical significance for continuous variables was obtained with T-test and Pearson Correlation while correlation between variables was obtained using Simple and Multiple Logistic Regression. Result: The prevalence of the asymptomatic gallstones patient for this study is 50.3% for the diabetic group and 49.7% for the non-diabetic group. For the diabetic group, the mean age for the patients was 59 years old (SD 8.9). Majority of them were in the group age of 50 to 59 years old (44%) and 60 years and above (41.7%). There was equal 50% for each gender in diabetic group. The male subset (n=36) showed increasing numbers of patients along with the age (40 to 49 years old 8.3%, 50 to 59 years old 44.4%, more than 60 years old 47.2%). In female subset, the percentage is highest in 50 to 59 years old group (44.4%). The 40 to 49 years old was 19.4% and more than 60 years old group was 36.1%. The races in diabetic this study showed that Malays were 88% in diabetic group while 91.5% in non-diabetic group.